Catheter Lock with Minocycline, EDTA and Ethanol for Salvaging of Central Venous Catheters in the Setting of Catheter-related Bloodstream Infections. (4th October 2017) - Hachem, Ray Y; Kanj, Souha; Hamerschlak, Nelson; Saad, Hala; Assir, Fernanda Ferraz; Mori, Nobuyoshi; Jiang, Ying; Ghaly, Fady; Chaftari, Anne-Marie; Raad, Issam
Abstract: Background: Long-term central venous catheters are essential in delivering care for critically ill and cancer patients. These catheters could lead to central line associated bloodstream infections (CLABSI). Removal and reinsertion of a new catheter may not always be feasible due to unavailability of vascular access in the setting of thrombocytopenia. A pilot open label study conducted at our institution showed promising results when Minocycline, EDTA, Ethanol (M-EDTA-EtOH) lock was used to salvage the catheter. Methods: Between October 2013 and August 2014, we prospectively enrolled 20 patients with catheter-related bloodstream infections (CRBSI) or CLABSI in three of our sister institutions in three countries including Brazil, Lebanon, and Japan. These patients received (M-EDTA-EtOH) lock therapy and were compared with 24 historical control patients who were matched based on organisms, underlying diseases and neutropenia status. The control patients had their CVCs removed and a new CVC inserted. Results: The two groups had comparable clinical characteristics. In the lock therapy group 95% of the patients had microbiological eradication within 96 hours after starting lock therapy vs. 83% of the patients in the control group ( P = 0.36). In the lock group, the CVC was salvaged and retained for a median of 21 days (range 7–51) from the onset of bacteremia whereas the CVC was removed after a median of 2 days in the control group (range 0–8 days. P < 0.0001). Conclusion: Our study suggests that M- EDTA-EtOH lock therapy seems to be an effective intervention to salvage long-term CVCs in the setting of CLABSI/CRBSI in cancer and dialysis patients with limited vascular access. Disclosures: I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol atheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty.